Understanding the Social Interaction of Drakor Squid Game Viewers in Financial Planning - Laela Agustina; Ayudia Sokarina (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The spread of the Korean Wave phenomenon around the word, one of which is Korean drama, is not only entertainment but also financial education. One of them is the Korean drama Squid Game which depicts extreme financial situations and games involting large amounts of money that can affect the audience’s perceptions and attitudes towards financial planning. This research aims to understand the social interaction of viewers of the squid game drama in financial planning. This research uses an interpretive paradigm and netnography as a research methodology. Researchers collected data passively and used multiple online platforms, including Instagram and TikTok. The data was analyzed using Coding, Noting, and Abstracting. The results of this research show that the social interaction of viewers of the Korean drama Squid Game in financial planning does not only focus on material aspects but also non-material aspects. In material terms, financial planning is used to gain profits, foster an anticipatory attitude, utilize debt, and reduce risk. On the other hand, financial planning in non-material terms is used to increase financial awareness, foster qana'ah, and foster rational and religious spiritual attitudes by paying attention to the welfare and happiness of the family while still thinking about the afterlife.